Crude : A Memoir - Fajardo, Pablo, 1972-; Tardy-Joubert, Sophie (Book collections on Project MUSE., 2021)
Oil waste was everywhere--on the roads, in the rivers where they fished, and in the water that they used for bathing, cooking, and washing. Children became sick and died, cases of stomach cancer skyrocketed, and women miscarried or gave birth to children with congenital disorders. The American oil company Texaco--now part of Chevron--extracted its first barrel of crude oil from Amazonian Ecuador in 1972. It left behind millions of gallons of spilled oil and more than eighteen million gallons of toxic waste. In Crude, Ecuadorian lawyer and activist Pablo Fajardo gives a firsthand account of Texaco's involvement in the Amazon as well as the ensuing legal battles between the oil company, the Ecuadorian government, and the region's inhabitants. As a teenager, Fajardo worked in the Amazonian oil fields, where he witnessed the consequences of Texaco/Chevron's indifference to the environment and to the inhabitants of the Amazon. Fajardo mobilized with his peers to seek reparations and in time became the lead counsel for UDAPT (Union of People Affected by Texaco), a group of more than thirty thousand small farmers and indigenous people from the northern Ecuadorian Amazon who continue to fight for reparations and remediation to this day.Eye-opening and galvanizing, Crude brings to light one of the least well-known but most important cases of environmental and racial injustice of our time.